Attività sperimentale di agricoltura di precisione su vigneto Confronto tra i sensori Mapir Survey2 e Parrot Sequoia - Simone Kartsiotis; Gianluca Rossetti; Matteo Turci; Emanuele Luigi de Angelis (GEOmedia, 2018)
This report presents a comparison via field-testing between Parrot Sequoia and Mapir Survey2 multispectral cameras. Both sensors are commonly used in precision farming activities conducted by micro-RPAS (drones), thanks to their small size and light weight. The experimental activity was performed in summer on the vineyards of the Savignola Paolina agricultural holding in Tuscany. The sensors were taken on board the EXOS drone, a hexacopter developed by Zephyr S.r.l. company and specifically designed for precision farming operations. Good and bad qualities for each cameras are examined by a comprehensive approach, starting from technical specifications and continuing with a comparison of the results obtained on field. All the activity was performed by a partnership between the companies DroneBee and Zephyr S.r.l. .